Proposta de elaboração de carta de sensibilidade ambiental aplicada a postos de combustíveis em Rio Claro-SP - Santos, Suseli de Marchi [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
Leaking of hydrocarbon in fuel underground storage tanks constitute object of concern for urban environmental management, because therefore they provoke damages to the physical, biological and socioeconomic environment. Though laws that regulate this essential activity exist, aiming at to prevent contamination with hydrocarbon, we observe that this still happens. This fact evidences that the selection of places for installation of gas stations has not considered the characteristics of the natural environment, implying in more critical consequences associated to the leaking. The objective of this work is to elaborate a chart applied to the gas stations in Rio Claro/SP. The determination of the Index of Environmental Sensitivity for elaboration of such chart was carried through breaking the selection of factors of Environmental Sensitivity of physical, biological and socioeconomic environment. The balance of these factors was given by means of Ad hoc consultation. The crossing of the information was carried through using the method of overlapping of overlays. The result is a chart that shows us areas with classes of high, middle and low Environmental Sensitivity. One gives credit that this type of material can be used as criterion in the selection of adjusted areas for installations of new gas stations and management of the already installed gas stations. The diagnosis of the current situation of the gas stations in the area and recommendations had also been elaborated.

Vazamentos de hidrocarbonetos em postos de combustíveis constituem objeto de preocupação para gestão ambiental urbana, pois provocam danos ao meio físico, biológico e socioeconômico. Embora existam legislações que regulam essa atividade essencial, visando evitar contaminação, observamos que essa ainda ocorre. Constata-se que a seleção de locais para instalação de postos de combustíveis não tem considerado as características do meio, implicando em conseqüências mais críticas associadas aos vazamentos. O objetivo desse trabalho é elaborar uma Carta de Sensibilidade Ambiental aplicada a postos de combustíveis em Rio Claro/SP. A determinação do Índice de Sensibilidade Ambiental para elaboração de tal carta foi realizada partindo-se da seleção de fatores de sensibilidade ambiental dos meios físico, biológico e socioeconômico. A ponderação desses fatores deu-se por meio de consulta Ad Hoc. O cruzamento das informações foi realizado utilizando-se do método de sobreposição de overlays em ambiente SIG, com auxílio do software ARCGIS. O resultado é uma carta que espacializa áreas com classes de sensibilidade ambiental alta, média e baixa. Acredita-se que esse tipo de material possa ser utilizado como critério na seleção de áreas adequadas para instalações e para gerenciamento dos postos já instalados. Foram elaborados também o diagnóstico da atual situação dos postos de combustíveis na área e recomendações técnicas e operacionais.
Keywords: Engenharia ambiental; Hidrocarbonetos; Postos de combustíveis; Carta de Sensibilidade Ambiental; Gas Stations; Environmental Sensitivity Charts; Hydrocarbon